Propionic and its combination with potassium sorbate can improve the utilisation and quality of sugarcane tops silage - Singh, Digvijay; Yadav, Ramdev; Tyagi, Nitin (Indian Journal of Dairy Science, 2021)
The objective of present study was to evaluate the effects of chemical additives on the quality parameters and nutritive value of sugarcane tops (SCT) silages. The trial was carried out in a completely randomized experimental design with total twelve treatments including two controls. The chemical additives (SB; Soidum benzoate, PS; Potassium sorbate, PA; propionic acid and their combinations) were applied onto the fresh SCT before ensiling @1.0% (wet basis) each, with common additives (0.5% Urea, 0.5% NaCl and 2% molasses on wet basis), and packed in 3.5 L vacuum sealed plastic jars of two replicates each. The analyzed variables were: chemical composition, quality parameters and nutritive values. Selection of most promising additive/combination was done with Flieg point and fitness values.Â  The addition of chemical additive before ensiling produced silages with better quality indices (pH, lactic acid, Flieg point and fitness values), higher nutritive value (crude protein and ME) and low NDF as compared to control. Ammonia Nitrogen (NH3N% TN) and protein fractionation (NDICP and ADICP) were also considered for the identification of best SCT top silage and chemical additive effect.Â  The results of present study suggested that PA and PS+PA were the most promising additive treatments for the improving the SCT silage quality and nutritive value. Furthermore, information extended from the present study is giving future direction towards animal feeding trials with SCT silage with chemical additive.